The architectural openings of the traditional courtyard "late straits" eclectic style shophouses, Penang case studies : lot nos. 3, 5 and 7 Lorong Ikan, George Town / Akram Zwain and Azizi Bahauddin - Zwain, Akram; Bahauddin, Azizi (2018)
Openings in the traditional courtyard shophouses buildings give facades a sense of scale and directional expression. For these reasons, it is important that care and sensitivity ought to be exercised in repairing existing openings as well as in designing new ones. It is to comprehend the remaining of the maintained culture in the heritage city of George Town. The Lot Nos. 3, 5 and 7 on Lorong Ikan built in 1929 are the typical shophouses along Lorong Ikan and are categorised as the Late Straits Eclectic Style in Penang. These buildings are examples of buildings and the case studies that embrace the original remaining components of the architectural heritage of George Town. This research aims to critically investigate the original openings elements preserved in these houses. The three lots were sold and were earmarked for conversion into a boutique hotel. This paper employed qualitative research approach that obtained data from the secondary sources and observation. The findings of the research point towards highlighting shop house openings, courtyard, air well centre opening, air vents, shutters and windows as well as the most important architectural openings elements preserved in this house which is an additional to its architectural character.